Analysis of the Influence of Economic and Educational Factors on the Unemployment Rate in Indonesia - Ayu Gracia Febrianti Hutapea; Christy Alicyanova Simatupang; Tamariska Tumanggor; Akmal Huda Nasution; Chairunnisa Zakina Adibra (Escalate : Economics and Business Journal, 2026)
This study aims to analyze the factors influencing the unemployment rate in Indonesia, particularly from economic and educational perspectives. The research employs a literature review method by examining relevant journals, books, and data from Statistics Indonesia. The findings indicate that economic factors such as economic growth, inflation, and minimum wages significantly affect the unemployment rate. Meanwhile, educational factors, including education level, skills, and the alignment between competencies and labor market demands, also play a crucial role in workforce absorption. However, the mismatch between education and industry needs, along with the lack of soft skills, remains a major cause of educated unemployment. Therefore, strong collaboration among the government, educational institutions, and industry is necessary to develop a competent workforce aligned with labor market demands.